On Regularization of a Source Identification Problem in a Parabolic PDE and Its Finite Dimensional Analysis (Journal of Partial Differential Equations, 2021)
"We consider the inverse problem of identifying a general source term, which is a function of both time variable and the spatial variable, in a parabolic PDE from the knowledge of boundary measurements of the solution on some portion of the lateral boundary. We transform this inverse problem into a problem of solving a compact linear operator equation. For the regularization of the operator equation with noisy data, we employ the standard Tikhonov regularization, and its finite dimensional realization is done using a discretization procedure involving the space $L^2(0,\\tau;L^2(\u03a9))$. For illustrating the specification of an a priori source condition, we have explicitly obtained the range space of the adjoint of the operator involved in the operator equation."
Keywords: Ill-posed; source identification; Tikhonov regularization; weak solution.